Prevalence, distribution and drug resistance of motile aeromonads in freshwater ornamental fishes - Abdulla, Mohamed Hatha Hatha M; John, Nifty (Indian Journal of Fisheries, 2012)
The objective of the present study was to assess the prevalence of various motile aeromonads in freshwater ornamental fishes and to elucidate the antibiogram and beta hemolytic activity among the isolates. A total of 120 ornamental fish samples were screened and analyzed for Aeromonas spp. Motile aeromonads were isolated from 37.5% of the ornamental fish samples. Various species of motile aeromonads such as Aeromonas caviae, Aeromonas hydrophila, Aeromonas jandaei, Aeromonas schubertii, Aeromonas sobria, Aeromonas trota and Aeromonas veronii were detected. All the isolates were sensitive to ceftazidime, chloramphenicol, ciprofloxacin and gentamicin. Multiple antibiotic resistance was observed in 58% of the isolates.